Ecological characteristics and distribution of Asarum balansae Franch. in Ban Bung, Na Hang district, Tuyen Quang province - Tuan, Nguyen Anh; Thai, Tran Huy (Academia Journal of Biology, 2012)
Asarum balansae Franch. is a perennial herbaceous plant, which began flowering from early October; flowers bloom in early December; ripe fruit and seed dispersal in July - August in the follwing year. Regeneration density of the plant was observed highest at the foot-hill of mountain (from 46,250 to 50,000 trees/ha), the plant originated from regeneration bud are dominant (from 76.6 to 97.5%), renewable particles have the relative low percentage (from 2.5 to 23.4%). At the mountain sides, the Asarum balansae is rarely observed, the regeneration desity is relatively low (from 0 to 417 trees/ha). The quality of regeneration is unequally observed in different areas: percentage of good, moderate and bad trees are 10 to 76.6%, 16.2 to 39% and 7.2 - 51%, res pectively. Asarum balansae distributes in the rain tropical forest in low land, altitude from 201 m to 600 m, concentrated in the valley along the trail at the foot-hill of mountain, they grow close to the soil surface, in the rich soil with humus; humidity, light porosity and high airflow; less coverage. The average distribution density is 42,083 trees/ha in forest structure comprising one timber floor at the foot-hill of mountain and two timber floor in mountain sides.